Understanding current transport at the Ni/GaN interface using low-frequency noise spectroscopy. (28th October 2016) - Kumar, Ashutosh; Kumar, V; Singh, R
Abstract: The non-ideal behaviour of the GaN-based Schottky diode is in general attributed to the combined effect of interface traps and barrier inhomogeneities at the metal/GaN interface. In our present work, we determine the relative contribution of these two non-idealities to electronic transport in Schottky barrier diodes, by using bias-dependent low-frequency noise measurements. Due to the single-trap-dominated electronic transport at lower bias, the noise spectra turn out to be Lorentzian, whereas the distribution in time constants available for interface states due to barrier inhomogeneities causes a deviation from Lorentzian towards a 1/ f -type noise spectrum in higher bias regions. The present study indicates that the shape of the noise spectrum, its level and variation with the applied bias, determine the dominant current transport mechanism at the Ni/GaN interface, which may be useful for improving the electrical behaviour of metal/GaN interfaces.